Sleep quality among emergency nurses and its influencing factors during COVID-19 pandemic: a cross-sectional study - Alrasheeday, Awatif; Alsaeed, Maha Ali; Alshammari, Bushra; Alshammari, Farhan; Alrashidi, Asia Saad; Alsaif, Turki Ahmed; Mahmoud, Soha Kamel; Cabansag, Dolores I.; Borja, Ma Venus; Alsayed, Ahmad R.; Elalem, Omaima Mohamed; Nageeb, Shaimaa Mohamed; et al. (Frontiers in Psychology, 2024)
Background COVID-19 has probably contributed to sleep disturbance among nurses, especially those working at emergency departments (EDs). Sleep disorders in nurse managers can negatively impact their health and impair work performance and decision-making. This study aimed to explore the quality of sleep among nurses working in EDs and its influencing factors during the COVID-19 pandemic. Method In this study, a cross-sectional design was employed to assess the sleep quality of nurses working in EDs during the COVID-19 pandemic. The research recruited a convenience sample of emergency nurses, who were selectively sourced from four hospitals in Hail City. This recruitment occurred over the period from April to July 2022. Descriptive data analysis was conducted using SPSS, with the significance level set at 0.05. Results Among the 216 participants in the study, the majority (55.6%) were aged between 30 and 39 years, and 73.6% were female. Additionally, 64.4% were married, while 69.4% had a bachelor’s degree, 20% held a diploma, and the remaining had a master’s degree. Notably, a significant 81.5% of the nurses reported poor sleep quality, as assessed by the Pittsburgh Sleep Quality Index (PSQI), with an overall mean score of 10.55 indicating poor sleep. The study highlighted that poor sleep quality among nurses was linked to being female, being married, and not exercising regularly. Better sleep was associated with nurses who manage fewer patients per shift and have adequate monthly income. Conclusion The prevalence of poor sleep quality among Emergency nurses during the COVID-19 pandemic is high. There is a pressing need for targeted interventions to enhance sleep quality among ED nurses. Improving sleep quality is not only essential for the wellbeing of these nurses but is also likely to contribute to better patient care.